Cirrhosis and partial portal thrombosis leading to severe variceal bleeding, an unusual presentation of sarcoidosis. Issue 4 (4th July 2022) - Moretti, Marco; Lefesvre, Pierre; Jonckheer, Joop
ABSTRACT: Introduction: Sarcoidosis is a systemic granulomatous disease, characterized by the formation of non-necrotizing granulomas. Even though granulomas are frequently found in liver biopsy, related symptoms rarely occur. In the current article, a case report is pictured to increase the knowledge on portal hypertension in hepatic sarcoidosis. Clinical situation: A 62-year-old female was diagnosed with variceal bleeding for which elastic banding was performed. The patient was admitted to the intensive care unit (ICU) as the bleeding persisted and she evolved in hemorrhagic shock. Liver ultrasound detected nodular hepatomegaly and partial portal thrombosis. Chest CT showed diffuse hilar adenopathies and interstitial micronodular lesion. Finally, PET-CT detected metabolic active liver, bone marrow, and upper and lower diaphragmatic adenopathies. Clinical resolution: Multidisciplinary discussion brought major advantages in rapid diagnosis and prompt effective treatment. Cirrhosis was diagnosed by liver nodularity on imaging and liver biopsy. Sarcoidosis diagnosis was supported by the biopsies of liver and lymph node, which yielded non-caseating granulomas infiltration. Chest CT scan and PET-CT were also consistent with this diagnosis. The complementary analysis excluded differential diagnosis. The patient was treated with high-dose methylprednisolone with notable clinical improvements and discharge from the ICU. Conclusion: Hepatic sarcoidosis can present as life-threatening bleeding due to variceal bleeding caused by portal hypertension. Differential diagnosis is broad when hepatic sarcoidosis is suspected. Therefore, a multidisciplinary discussion is warranted. Anatomopathological examination of two potentially involved organs should be considered to make the appropriate diagnosis. Further studies are requested to investigate the pathophysiological mechanism of portal hypertension.